Buying Into English : Language and Investment in The New Capitalist World - Catherine Prendergast (University of Pittsburgh Press, 2008)
Based on extensive fieldwork in Slovakia, the author record the thoughts, aspirations, and concerns of slavak nationals, laguage instructors, journalists, abd textbook author who contend with the increasing importance of English in their rapidly evolving world.